2008
DOI: 10.1634/stemcells.2008-0141
|View full text |Cite
|
Sign up to set email alerts
|

Urokinase Plasminogen Activator and Urokinase Plasminogen Activator Receptor Mediate Human Stem Cell Tropism to Malignant Solid Tumors

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(65 citation statements)
references
References 38 publications
1
59
0
4
Order By: Relevance
“…The direct link between uPA and cancer stem cells (CSCs) or MDR proteins has not been reported. Gutova et al (2008) have recently shown that uPA can mediate human stem cell tropism to malignant solid tumours by chemotaxis and cell guidance. Here, we first showed the colocalisation of uPA and CD44 in primary and metastatic EOC cells, and the direct link between uPA and MDR proteins (MDR1 and MRP2).…”
Section: Discussionmentioning
confidence: 99%
“…The direct link between uPA and cancer stem cells (CSCs) or MDR proteins has not been reported. Gutova et al (2008) have recently shown that uPA can mediate human stem cell tropism to malignant solid tumours by chemotaxis and cell guidance. Here, we first showed the colocalisation of uPA and CD44 in primary and metastatic EOC cells, and the direct link between uPA and MDR proteins (MDR1 and MRP2).…”
Section: Discussionmentioning
confidence: 99%
“…Early on, due to the high affinity of HSCs and their leukocyte progeny for wound and tumor sites, investigators looked to the already wellcharacterized processes of HSC and leukocyte homing for clues driving MSC migration. 96,97 Indeed, factors involved in HSC and immunocyte recruitment, such as monocyte chemotactic protein-1 (MCP-1), 98 stromal-cell derived factor (SDF-1), 99 cyclophilin B and hepatoma-derived growth factor (HDGF), 100 urokinase plasminogen activator (uPA), 101,102 interleukin (IL-)6, 103 basic fibroblast growth factor (bFGF) 104 and vascular endothelial growth factor (VEGF) 104 have all been implicated in driving the tropism of bone-marrow-derived MSCs to tumors. It is believed that an active inflammatory response is necessary to allow MSC recruitment to tumor sites.…”
Section: Msc Homing To Tumorsmentioning
confidence: 99%
“…(28). Secreted ligands may be recognized by HB1.F3.yCD cells, and a tumor specific migratory property may be stimulated by these stem cells (29).…”
Section: Discussionmentioning
confidence: 99%